Response of Biostimulants on Growth, Flowering, Seed Yield and Quality of China Aster (Callistephus chinensis (L.) Nees) - Pathania, S.; Dilta, B. S.; Kumar, A. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted to evaluate the effect of different concentrations of Jeevamrit applied both as drench and foliar spray and Trichoderma spp @ 1 kg q-1 FYM+Foliar application of Neem seed kernel extract and Garlic extract @ 5% each at 15 days interval on growth and flowering parameters in China aster cv. ‘Kamini’. Findings revealed that maximum plant height (47.38 cm), plant spread (28.47 cm), number of flowers plant-1 (23.87), number of flowers plot-1 (286.44), number of seeds flower-1 (160.27), seed yield plant-1 (8.03 g), seed yield plot-1 (96.40 g), were recorded with treatment application of Jeevamrit @ 5% (Drench)+foliar application of Jeevamrit @ 10%. Maximum flower diameter (5.81 cm), individual flower weight (3.91 g), 100 flower weight (393.31 g), 1000 seed weight (2.20 g), were recorded with Jeevamrit @ 7.5% (Drench)+Foliar application of Jeevamrit @ 10% application. Soil treatment with Trichoderma spp @ 1 kg q-1 FYM+Foliar application of Neem seed kernel extract and Garlic extract @ 5% each at 15 days interval, alternatively proved best for seed quality parameters viz., EC (60.25 ds m-1), germination percentage (84.75%), seedling length (6.22 cm), seedling dry weight (4.18 mg), seed vigour index-I (527.15), seed vigour index-II (354.26).